Japanese Society for Burn Injuries (JSBI) Clinical Practice Guidelines for Management of Burn Care (3rd Edition). Issue 1 (27th April 2022) - Sasaki, Junichi; Matsushima, Asako; Ikeda, Hiroto; Inoue, Yoshiaki; Katahira, Jiro; Kishibe, Miyuki; Kimura, Chu; Sato, Yukio; Takuma, Kiyotsugu; Tanaka, Katsumi; Hayashi, Minoru; Matsumura, Hajime; et al.
Abstract : The Japanese Society for Burn Injuries (JSBI) published the third edition of guidelines to present the standard of care for inpatient treatment of burn injuries in Japan. The guideline is not a mere revision of the first and second editions but has been carefully designed to be user friendly and of high quality for medical professionals engaged in burn care. We think it is important to share these guidelines with other countries to work toward a consensus of burn care, then develop new research to establish evidence for burn care and treatment in the future.